2019
DOI: 10.1002/mgg3.844
|View full text |Cite
|
Sign up to set email alerts
|

Skin fibroblasts of patients with geleophysic dysplasia due to FBN1 mutations have lysosomal inclusions and losartan improves their microfibril deposition defect

Abstract: Background Geleophysic dysplasia (GPHYSD) is a disorder characterized by dysmorphic features, stiff joints and cardiac involvement due to defects of TGF‐β signaling. GPHYSD can be caused by mutations in FBN1, ADAMTLS2, and LTBP3 genes. Methods and Results Consistent with previous reports, we found intracellular inclusions of unknown material by electron microscopy (EM) in skin fibroblasts of two GPHYSD individuals carrying FBN1 mutations. Moreover, we found that the storage material is enclosed within lysosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Similar inclusions were also found in bronchial epithelial cells of Adamtsl2 − / − mouse, thus suggesting glycogen storage [8]. Moreover, we previously found that inclusions are also present in fibroblasts of GPHYSD patients carrying FBN1 mutations and Myhre syndrome (MIM139210) patients carrying SMAD4 mutations [26], suggesting that a common pathway is responsible for the formation of such inclusions. Here, we showed that lysosomal inclusions do not appear to contain mutant ADAMTSL2.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Similar inclusions were also found in bronchial epithelial cells of Adamtsl2 − / − mouse, thus suggesting glycogen storage [8]. Moreover, we previously found that inclusions are also present in fibroblasts of GPHYSD patients carrying FBN1 mutations and Myhre syndrome (MIM139210) patients carrying SMAD4 mutations [26], suggesting that a common pathway is responsible for the formation of such inclusions. Here, we showed that lysosomal inclusions do not appear to contain mutant ADAMTSL2.…”
Section: Discussionsupporting
confidence: 55%
“…Intracellular inclusion bodies were previously reported in GPHYSD cases [2,24,25] and we recently found that storage occurs within lysosomes in GPHYSD cells carrying FBN1 mutation [26]. Primary fibroblasts from skin biopsy available only for subject 3 were analyzed by EM and showed lysosomal-like vesicles with lamellar structure appearance and electron-dense storage material (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Losartan potassium salt (Sigma Aldrich, Milan, Italy) was dissolved into dimethyl sulfoxide (DMSO) (Sigma Aldrich, Milan, Italy) and used at the concentration of 200 µM for 14 days on controls’ and patient’s fibroblast cultures as reported in [ 64 , 65 ]. Skin fibroblast cell cultures from the patient and control at 2 passages were seeded (2 × 10 5 cells/mL in six-well plates) and after 24 h were incubated with losartan in a single dose in DMEM/F-12 with 20% FBS medium.…”
Section: Methodsmentioning
confidence: 99%
“…Cultured aortic vascular smooth muscle cells were used to explore extracellular matrix abnormalities associated with MFS and bicuspid aortic valve ( Nataatmadja et al 2003 ). Fibroblasts from a patient with geleophysic dysplasia due to a variant in FBN1 were used to test the effect of losartan treatment and results suggested that this would be a promising treatment for these patients ( Piccolo et al 2019 ). FBN2 is also expressed by fibroblasts and its role in the response to hypoxia has been investigated in fibroblast cultures ( Boizot et al 2022 ).…”
Section: Other Potential Models For Fibrillinopathiesmentioning
confidence: 99%